The Seasonal Origins of Streamwater in Switzerland. Issue 17 (3rd September 2019) - Allen, Scott T.; von Freyberg, Jana; Weiler, Markus; Goldsmith, Gregory R.; Kirchner, James W.
Abstract: Quantifying the relative contributions of winter versus summer precipitation to streamflow may be important for understanding water‐resource sensitivity to precipitation variability. Here we compare volume‐weighted mean δ 18 O values in precipitation and streamflow for 12 catchments in Switzerland, to determine whether summer or winter precipitation is overrepresented in streamflow, relative to its proportion of total precipitation. Similarities between precipitation and streamflow weighted‐mean δ 18 O values indicate that roughly equal fractions of summer and winter precipitation supply streams in Switzerland. These results, together with mass conservation, suggest that similar fractions of summer and winter precipitation supply evapotranspiration. These findings contrast with the assumption that because summer precipitation falls when transpiration rates and evaporative demand are high, it should be underrepresented in streamflow and overrepresented in evapotranspiration. This contrast between seasonal water‐balance variations and the partitioning of seasonal precipitation into runoff and evapotranspiration demonstrates substantial interseasonal carryover of precipitation in storages that supply evapotranspiration. Plain Language Summary: Precipitation inputs often greatly exceed streamflow outputs during the summer in seasonal climates because evapotranspiration rates are much higher in summer than in winter. Such seasonal water balance variations often lead to the expectation that smaller proportions of summer precipitation and larger proportions of winter precipitation eventually become streamflow. We tested which seasons' precipitation was overrepresented in streamflow, relative to their proportions of total precipitation. We did this using the stable isotope ratios of precipitation—which are distinctly heavier in summer than in winter—and streamflow in 12 streams in Switzerland. We found that the volume‐weighted averages of precipitation and streamflow were isotopically similar, implying that neither season is overrepresented in streamflow. Thus, the fraction of summer precipitation that becomes streamflow roughly equals the fraction of winter precipitation that becomes streamflow. Our results potentially suggest that streamflow and evapotranspiration, including the use of water by plants during growing seasons, may both be sensitive to fluctuations in summer and winter precipitation. Key Points: We tested whether summer or winter precipitation is overrepresented in streamflow relative to its proportion of total precipitation Oxygen‐18 ratios in streams indicate that similar fractions of summer and winter precipitation become discharge in Switzerland Interseasonal storage can explain why the seasonal partitioning of precipitation differed substantially from the seasonal water balance